Sustainable preservation of lanna palm leaf manuscripts based on community participation - Piyapat Jarusawat (2020)
© 2020, The International Academic Forum (IAFOR). All rights reserved. Palm leaf manuscripts (PLMs), with their strong bond to Buddhism, are one invaluable symbol of the Lanna culture of Northern Thailand. This study investigates the views about PLM management among local people in the Pa Tum Don community, Chiang Mai province, Thailand, and explores the potential for them to sustain the preservation of PLMs. A thematic analysis of semi-structured interviews with community members found that they engage in activities related to PLMs because of their continued faith in the goodness in them. Although it is mostly older people that have been very active participants in preserving PLMs, they lack systematic preservation knowledge. Aside from digitization, establishing rituals using and reproducing PLMs, transferring linguistic knowledge and reinserting Lanna language into fundamental education are suggested as possible means to enable sustainable preservation.